2004
DOI: 10.1677/jme.0.0320021
|View full text |Cite
|
Sign up to set email alerts
|

Expression and signalling characteristics of the corticotrophin-releasing hormone receptors during the implantation phase in the human endometrium

Abstract: Corticotrophin-releasing hormone (CRH) has been identified in several peripheral tissues, including the female reproductive organs. CRH is expressed in the placenta, myometrium, epithelial endometrium and the endometrial stromal cells at all phases of the menstrual cycle. Similarly, CRH receptors are present in pregnant and non-pregnant myometrium, placenta and endometrium. Putative roles of CRH in the endometrium include involvement in implantation, decidualisation and maintenance of pregnancy. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
2
26
0
1
Order By: Relevance
“…Similar to previous findings by other groups (Di Blasio et al, 1997, Karteris et al, 2004, we found that CRH-R1 is expressed in the cytoplasm of normal epithelial endometrial cells. Most importantly, CRH-R1 expression was found in a higher percentage of tumors expressing progesterone receptors, indicating that CRH-R1 expression is associated to a more differentiated and less aggressive phenotype.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to previous findings by other groups (Di Blasio et al, 1997, Karteris et al, 2004, we found that CRH-R1 is expressed in the cytoplasm of normal epithelial endometrial cells. Most importantly, CRH-R1 expression was found in a higher percentage of tumors expressing progesterone receptors, indicating that CRH-R1 expression is associated to a more differentiated and less aggressive phenotype.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it was interesting to investigate the expression and localization of such receptor subtype in our paradigm. Human endometrial cells were shown to express CRH-R2 under physiological conditions (Karteris et al, 2004); in the present study, we could confirm CRH-R2 expression in normal endometrial tissues surrounding the tumor; moreover, we observed an unprecedented nuclear localization, whose functional meaning remains to be established. Conversely, the expression of CRH-R2 in the tumor cell cytoplasm has been more frequently observed in stage II-IV compared to stage I tumors, thus suggesting that high CRH-R2 might identify poor prognosis tumors.…”
Section: Discussionsupporting
confidence: 62%
“…The human-specific CRH-R1␤ receptor variant, which is identical to the CRH-R1␣ except for a 29-amino acid insert in the first intracellular loop, interacts with CRH and G s with significantly reduced agonist affinity compared with CRH-R1␣ (Xiong et al, 1995). Like many other splice variants, the CRH-R1␤ mRNA expression exhibits tissue-specific characteristics and has been identified in anterior pituitary, myometrial smooth muscle cells, and endometrium and human umbilical cord blood mast cells (Chen et al, 1993;Grammatopoulos et al, 1998;Slominski et al, 2001;Karteris et al, 2004;Cao et al, 2005) but not in the placenta, adrenal, and synovium (Karteris et al, , 2001McEvoy et al, 2001). The function(s) of CRH-R1␤ and the potential CRH-R1-derived receptor variants is currently unknown.…”
mentioning
confidence: 99%
“…In addition, the human endometrium also expresses both CRF-R1 (Di Blasio et al 1997) and CRF-R2 (Karteris et al 2004), and in in vitro experimental models, the activation of the cAMP pathway induced by the binding to CRF-R1 located on endometrial stromal cells demonstrated differentiating activity, since those cells undergo decidualization (Ferrari et al 1995). Furthermore, the activation of CRF-R1 receptor subtype, which is expressed under basal conditions by a tumor cell line derived from the human endometrium, namely adenocarcinoma Ishikawa cells, inhibits tumor cell growth, and proliferation in a dose-and time-dependent manner (Graziani et al 2002).…”
Section: Introductionmentioning
confidence: 99%